Retention of omega-3 fatty acids (DHA and EPA) and cooking yield in fish cooked using wet-heat methods: Steaming vs. bake-in-foil - Muhammad Alinafiah, Suryati; Azlan, Azrina; Ismail, Amin; Mahmud @ Ab Rashid, Nor Khaizura (Academic Press, 2025)
Regular fish consumption is recommended by health organizations to enhance omega-3 intake, reducing cardiovascular disease risk. Cooking enhances food's physical properties and nutritional value but may degrade essential omega-3 fatty acids, EPA and DHA. This study evaluates the impact of two wet-heat cooking methods (steaming and baking in foil) on the retention of EPA and DHA in three fish species: Indian Scad (SF), Indian Mackerel (KF), and Moonfish (MF). Results indicated steaming preserved PUFA better than baking in foil (BIF) across all samples. In steaming, EPA retention was highest in KF (60.4%), followed by SF (54.6%) and MF (6.1%); DHA retention mirrored the trend. In BIF, KF retained more EPA (36.8%) and DHA (38.1%) than SF and MF. Cooking yields (CY) varied, with SF having the highest yield in steaming (84.8%) and MF in BIF (79.4%). Steamed SF provided the highest total EPA + DHA (>500 mg/100 g) among all samples. The superior retention of DHA and EPA by steaming is likely due to its lower temperature (100°C) than BIF (160°C). These findings strongly support the preference for steaming over BIF, for retaining EPA, DHA in fish, particularly SF, which may serve as an excellent EPA, DHA dietary source for cardiovascular health.